Antibiotic Susceptibility Profile of Aeromonas Species Isolated from Wastewater Treatment Plant - Isoken H. Igbinosa; Anthony I. Okoh (The Scientific World Journal)
This study assessed the prevalence of antibiotic-resistant Aeromonas species isolated from Alice and Fort Beaufort wastewater treatment plant in the Eastern Cape Province of South Africa. Antibiotic susceptibility was determined using the disc diffusion method, and polymerase chain reaction (PCR) assay was employed for the detection of antibiotics resistance genes. Variable susceptibilities were observed against ciprofloxacin, chloramphenicol, nalidixic acid, gentamicin, minocycline, among others. Aeromonas isolates from both locations were 100% resistant to penicillin, oxacillin, ampicillin, and vancomycin. Higher phenotypic resistance was observed in isolates from Fort Beaufort compared to isolates from Alice. Class A pse1 β-lactamase was detected in 20.8% of the isolates with a lower detection rate of 8.3% for blaTEM gene. Class 1 integron was present in 20.8% of Aeromonas isolates while class 2 integron and TetC gene were not detected in any isolate. The antibiotic resistance phenotypes observed in the isolates and the presence of β-lactamases genes detected in some isolates are of clinical and public health concern as this has consequences for antimicrobial chemotherapy of infections associated with Aeromonas species. This study further supports wastewater as potential reservoirs of antibiotic resistance determinants in the environment.